Peningkatan Pengetahuan Lansia Tentang Pencegahan Stroke Melalui Edukasi Pengendalian Hipertensi dan Diabetes Melitus - Mike Asmaria; Vivi Yuderna; Mariza Elvira; Armaita Armaita; Ramaita Ramaita (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Stroke is a leading cause of death and disability, closely associated with hypertension and diabetes mellitus as major risk factors. This community service activity aimed to improve public knowledge about hypertension and diabetes mellitus as a stroke prevention effort in Nagari Pakadangan, Padang Pariaman Regency. The method used was health education through counseling, discussion, and question-and-answer sessions. The activity began with blood pressure and blood glucose checks and a pre-test, followed by educational material using audiovisual media, and ended with a post-test. The participants consisted of 20 elderly individuals accompanied by health workers and cadres. The results showed an increase in participants' knowledge after the intervention. Before counseling, 7 participants (35%) had high knowledge and 13 participants (65%) had low knowledge. After counseling, high knowledge increased to 16 participants (80%) while low knowledge decreased to 4 participants (20%). Health education was proven effective in improving public knowledge regarding stroke prevention through hypertension and diabetes mellitus control.